Ayat-Ayat Makrifatullah dalam Tafsir Al-Qur’an Al-‘Azhim Karya Sahl Al-Tustari - Luthviyah Romziana; Lola Amalia (IAIN Bengkulu, 2023)
Makrifat in the view of the Sufi is to know how the true nature of God is. In the world of tasawuf, makrifatullah is an important thing in spiritual formation. As happened in modern times, many negative impacts occur due to a lack of relevance to the spiritual aspect, so Sufism is needed to balance these dimensions. This study aims to explain the interpretation of makrifatullah verses according to Sahl al-Tustari in the book of Tafsir al-Qur'an al-'Azhim. This research is a qualitative research using a literature study approach. The analytical method used is content descriptive analysis technique. The results of this study indicate that makrifat in the Qur'an means knowing, knowing, acknowledging His Oneness and Omnipotence by thinking through His signs, increasing spirituality by carrying out religious obligations and avoiding His prohibitions, bowing to the Qur'an and hadith, having a sincere nature , always repent, have a calm soul, always remember Him under any circumstances. Sahl al-Tustari explained that to get protection from immoral acts, namely by makrifat. The results of this study are useful if they can be practiced to cleanse the heart which leads to harmony in life, closeness, obedience and piety to Allah in the formation of good morals